Legal Status of Traditional Fish Spices in Indonesian Fisheries Law: Status Hukum Bumbu Ikan Tradisional dalam Undang-Undang Perikanan Indonesia - Rayhan Wahyu Wijaya; Sri Budi Purwaningsih (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Sustainable fisheries governance requires balancing environmental protection with the preservation of indigenous practices and community-based resource management. Specific Background: In several Indonesian regions, traditional fish spices derived from natural plants such as tuba, acacia, and sago are used in small-scale fishing and are regarded as part of inherited local wisdom. However, these practices are often perceived as equivalent to the use of chemical fish poisons, which are explicitly prohibited by national fisheries regulations. Knowledge Gap: Existing legal scholarship largely concentrates on destructive fishing methods using synthetic chemicals, while the juridical status of traditional plant-based substances within positive law remains insufficiently examined. Aims: This study analyzes whether traditional fish spices can be legally equated with chemical fish poisons under Indonesian fisheries, health, and chemical regulations using a normative juridical approach. Results: The analysis shows that traditional spices possess mild, biodegradable toxicity, are applied in limited quantities, and function selectively within small aquatic areas, whereas chemical poisons are highly toxic, persistent, non-selective, and environmentally destructive; consequently, traditional spices cannot be classified as prohibited poisons. Novelty: The study offers a legal interpretation that situates traditional plant-based fishing substances within the framework of local wisdom and sustainable resource use rather than within categories of banned hazardous materials. Implications: Policymakers should develop adaptive regulatory mechanisms that recognize cultural practices while ensuring environmental safeguards and supervision to maintain ecological sustainability. Highlights: Plant-derived substances used in customary fishing differ fundamentally from synthetic toxic agents in composition, persistence, and ecological scope. National regulations prohibit hazardous chemicals but allow space for culturally rooted resource practices under supervision. Recognition of community traditions can coexist with aquatic ecosystem protection through context-sensitive governance. Keywords:Traditional Fish Spices; Fisheries Law; Local Wisdom; Chemical Fish Poison; Environmental Sustainability